Voltage Compensation Using Dvr with Modified Switching Band Control - Rao, Sura.Srinivasa; Babu, Choppavarapu.Sai (International Journal of Engineering and Technology, 2018)
This paper presents mitigation of voltage related Power Quality (PQ) issues by using Dynamic Voltage Restorer (DVR). Three phase four wire DVR with modified switching band controller is proposed. A modified filter circuit band controller is proposed for reducing the switching losses, constant switching frequency maintenance and corresponding simulation studies are carried out. Variable hysteresis band (modified band) controller generates accurate injected voltages by using system parameters and low error value between reference injected voltages, actual injected voltages can be achieved, which helps in smoothening and minimizing ripples in PCC (Point of common coupling) voltages. The obtained simulation results are presented.